PENGARUH KOMPENSASI FINANSIAL, MOTIVASI BERPRESTASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PERUM DAMRI DIVISI REGIONAL II SEMARANG - Sutopo, SE, M.Si; Volta Mohamad Brilian (LPPM STIE DHARMAPUTRA SEMARANG, 2026)
The objective of this study is to analyze the influence of financial compensation, achievement motivation, and career development on employee performance. The study population consists of all 64 employees in the finished goods loading warehouse division at Perum DAMRI Regional Division II Semarang; the entire population was sampled using the census method. Multiple regression was employed as the data analysis method. The analysis results confirm Hypothesis 1 (H1), showing that financial compensation has a positive effect on employee performance. The regression coefficient for the financial compensation variable is positive, indicating that the more satisfactory the financial compensation received by employees, the higher their performance. Hypothesis 2 (H2) is also confirmed, demonstrating that achievement motivation positively affects employee performance. The positive regression coefficient for the achievement motivation variable implies that higher achievement motivation leads to higher employee performance. Finally, Hypothesis 3 (H3) is confirmed, showing that career development has a positive effect on employee performance. The positive regression coefficient for the career development variable indicates that the more optimal the career development programs implemented by the company, the higher the employee performance.Keywords : Financial compensation, achievement motivation, career development, employee performance